Coupled cross-flow and in-line vibration characteristics of frequency-locking of marine composite riser subjected to gas-liquid multiphase internal flow. (15th December 2022) - Chang, X.P.; Qu, C.J.; Song, Q.; Li, Y.H.; Liu, J.
Abstract: In this paper, the frequency locking characteristics of marine composite riser coupled with cross-flow (CF) and in-line (IL) under the combined action of internal and external ocean currents in gas-liquid multiphase transportation are studied. Based on Hamilton's variational principle, the coupled vibration control equations of composite marine riser in CF and IL directions were established considering the combined action of internal and external ocean currents in gas-liquid multiphase transport. The Van der Pol wake oscillator model was used to simulate the flow force of the ocean current on the CF and IL directions of the slender riser. Newmark- β and fourth-order Runge-Kutta coupling iterative method were used to solve the coupled dynamics equation. The effectiveness and accuracy of the proposed method were verified by comparing with the results in literature. Subsequently, the effects of liquid phase velocity, fiber orientation angle and top axial tension on the frequency-locking characteristics of marine riser were given. The research results show that the internal flow velocity, external ocean current velocity, fiber orientation angle and top axial tension have a great influence on the coupled vibration stability and frequency locking characteristics of the riser. In addition, compared with the uniform single internal flow, the critical value of the velocity of the gas-liquid multiphase mixed internal flow is larger; The frequency-locking interval of the riser "shifts to the right" with the increase of liquid flow velocity and fiber orientation angle, and "shifts to the left" with the increase of top axial tension. It is also found that the frequency locking range of the riser decreases with the increase of fiber orientation angle and top axial tension, and expands with the increase of liquid flow velocity. Highlights: A dynamic prediction model of coupled VIV of composite riser under gas-liquid two-phase internal flow is proposed. The coupled Runge-Kutta method and Newmark-β method are used to solve the dynamic prediction model and wake oscillator model. The critical velocity of the riser with gas-liquid multiphase mixed internal flow is larger. The frequency locking range of riser decreases with the increase of fiber orientation angle and top axial tension.